Comparison Between Gleason Score and Apparent Diffusion Coefficient Obtained from Diffusion-Weighted Imaging of Prostate Cancer Patients. (1st November 2013) - Caivano, Rocchina; Rabasco, Paola; Lotumolo, Antonella; Cirillo, Patrizia; D'Antuono, Felice; Zandolino, Alexis; Villonio, Antonio; Macarini, Luca; Salvatore, Marco; Cammarota, Aldo
Abstract : Objectives: To correlate the apparent diffusion coefficient (ADC) of prostate cancer patients with pathological Gleason scores (GS). Methods : 40 patients with GS 2 + 3, 3 + 3, 3 + 4, or 4 + 4 were selected. The magnetic resonance imaging (MRI) study was performed adding axial diffusion-weighted imaging (DWI) sequences to the standard MRI protocol. ADC values obtained were correlated with the GS data. Results : Statistically significant differences of ADC ( p < .05) were found among GS groups with a trend of decreasing ADC values with increasing GS. Conclusions : The ADC values may help clinicians to delineate prostate carcinoma, recognizing its high- or low-grade compartments.